The deverbal nominalization in The word of the Dead or Ayacucho Hora Nona - Amaringo Caballero, Diana (2022)
In this paper, a case study of nominalization in the poem "La palabra de los muertos o Ayacucho hora nona" by Marcial Molina Richter (1991) is carried out. The aim of this study is to provide a model for the study of the function of deverbal words of action and effect. In addition, it will allow us to discover the advantages of this new style of interpretation of the verses embodied in poetic discourses. The method of work is stylistics in morphological strategies of nominal and verbal syntagma. Subjected to the language of the environment. The aim is, therefore, to carry out a stylistic analysis of the use of these units from the methodological parameters of the concept of nominalization, in addition it is intended to clarify the characteristics of the nominalization process through the use of various suffixes in the poetic work of Marcial Molina Richter.